2013
DOI: 10.1007/s11606-013-2516-z
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Neighborhood Socioeconomic Status and Race on the Prescribing of Opioids in Emergency Departments Throughout the United States

Abstract: BACKGROUND: Racial and ethnic disparities in opioid prescribing in the emergency department (ED) are well described, yet the influence of socioeconomic status (SES) remains unclear. OBJECTIVES: (1) To examine the effect of neighborhood SES on the prescribing of opioids for moderate to severe pain; and (2) to determine if racial disparities in opioid prescribing persist after accounting for SES. DESIGN: We used cross-sectional data from the National Hospital Ambulatory Medical Care Survey between 2006 and 2009 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
110
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(117 citation statements)
references
References 25 publications
2
110
5
Order By: Relevance
“…26 Ndlovu 26 also found that the majority of patients received no pharmacologic therapy, much the same as this study. However, this study presents contrast with the findings of Joynt et al 15 , which noted low nSES was associated with a 24% decrease in odds of opioid prescription. However, the study by Joynt et al 15 was based in the emergency room (ER) where ap- proaches to care may be different.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…26 Ndlovu 26 also found that the majority of patients received no pharmacologic therapy, much the same as this study. However, this study presents contrast with the findings of Joynt et al 15 , which noted low nSES was associated with a 24% decrease in odds of opioid prescription. However, the study by Joynt et al 15 was based in the emergency room (ER) where ap- proaches to care may be different.…”
Section: Discussioncontrasting
confidence: 99%
“…However, this study presents contrast with the findings of Joynt et al 15 , which noted low nSES was associated with a 24% decrease in odds of opioid prescription. However, the study by Joynt et al 15 was based in the emergency room (ER) where ap- proaches to care may be different. Further, the provider-patient relationship in the ER environment is likely quite different from the primary care setting as well.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…1 Patients from poorer neighborhoods and African-Americans and Latinos were less likely to be prescribed opioids. The effects for race and ethnicity persisted even when neighborhood factors were controlled.…”
mentioning
confidence: 99%